Annual World Bank Conference on Development Economics 2004, Europe are we on track to achieve the millennium development goals? (Washington, D.C. Copublication of the World Bank and Oxford University Press, 2005)
"Annual World Bank Conference on Development Economics Europe 2005 presents selected papers from the sixth annual ABCDE - Europe meetings, held May 2004 in Brussels, Belgium. This volume contains articles on trade flows, human capital flows, capital f lows and aid flows. It provides a general overview of the links between poverty and migration and insight and opinions on key development issues."
Includes bibliographical references.
Keywords: Development economics -- Periodicals; Europe -- Economic conditions -- Periodicals; Europe -- Economic policy -- Periodicals